Pelatihan Kerajinan Tempat Tisu Berbahan Kerang sebagai Strategi Pemberdayaan UMKM Lokal - Anggit Dyah Kusumastuti; Luluk Nur Aulia (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
The The seashell tissue box craft training was conducted as a community empowerment initiative aimed at strengthening local Micro, Small, and Medium Enterprises (MSMEs) through the development of value-added handicraft products based on coastal resources. This program sought to enhance participants’ knowledge, practical skills, and creativity in transforming seashells into aesthetically appealing and marketable tissue boxes with economic value. The training was implemented through several stages, including preparation, theoretical sessions on entrepreneurship and product development, hands-on demonstrations, guided practice, and evaluation of participants’ final products. Participants received comprehensive instruction on selecting and cleaning seashells, designing product layouts, applying appropriate assembly techniques, and performing finishing processes to produce durable and attractive handicrafts. The results indicated a significant improvement in participants’ technical abilities and understanding of product innovation, quality enhancement, and marketing strategies for expanding business opportunities. The high level of enthusiasm and active involvement throughout the training reflected the community’s strong interest in developing creative industries based on local resources. Therefore, seashell tissue box craft training represents an effective strategy for empowering local MSMEs by encouraging innovation, increasing product competitiveness, and creating sustainable economic opportunities that contribute to improving community income and local economic development. Keywords: seashell handicrafts, MSME empowerment, tissue box crafts, local resources, community training.   Abstrak Pelatihan kerajinan tempat tisu berbahan kerang dilaksanakan sebagai salah satu strategi pemberdayaan UMKM lokal melalui pengembangan produk kerajinan yang memanfaatkan potensi sumber daya pesisir. Kegiatan ini bertujuan untuk meningkatkan pengetahuan, keterampilan, dan kreativitas peserta dalam mengolah limbah serta kerang laut menjadi produk bernilai ekonomi yang memiliki daya saing di pasar. Metode pelaksanaan meliputi tahap persiapan, penyampaian materi mengenai peluang usaha dan teknik pembuatan kerajinan, demonstrasi, praktik langsung, serta evaluasi hasil karya peserta. Dalam pelatihan, peserta dibimbing mulai dari proses pemilihan dan pembersihan kerang, penyusunan desain, teknik penempelan pada media tempat tisu, hingga tahap finishing agar menghasilkan produk yang menarik, rapi, dan memiliki nilai jual. Hasil kegiatan menunjukkan adanya peningkatan kemampuan peserta dalam menghasilkan produk kerajinan yang lebih kreatif dan berkualitas, sekaligus meningkatkan pemahaman mengenai pentingnya inovasi produk dan pemasaran sebagai upaya pengembangan usaha. Antusiasme peserta selama kegiatan juga menunjukkan bahwa pelatihan berbasis potesi lokal mampu menjadi alternatif pemberdayaan ekonomi masyarakat. Dengan demikian, pelatihan kerajinan tempat tisu berbahan kerang dapat menjadi salah satu upaya yang efektif dalam meningkatkan kapasitas UMKM lokal melalui penciptaan produk kreatif yang bernilai tambah serta berpotensi mendukung peningkatan pendapatan masyarakat.